Apakah Kualitas Audit Berpengaruh terhadap Penghindaran Pajak? - Purnomo, Hanny (Jurnal Ekonomi Akuntansi dan Manajemen, 2025)
Tax avoidance is a crucial issue that affects the stability of the country's economy. This research examines the influence of one of the Good Corporate Governance mechanisms, namely audit quality on tax avoidance. This research uses a sample of 504 companies from all sectors except finance on the Indonesia Stock Exchange for the 2019-2022 period. The research results show that audit quality as reflected by the size of the Public Accounting Firm and Audit Fees does not affect tax avoidance. The implications of this research focus on increasing taxpayer awareness and improving tax regulations to minimize tax avoidance. Keywords:  Audit Firm Size, Audit Quality, Corporate Governance, Tax Avoidance, Audit Fee